Antecedents of the adoption of social media policy and its consequences towards internal brand: a conceptual paper - Halil, Nur Afni; Bidin, Rosmiza; Osman, Mohd Nizam; Syed Alsagoff, Syed Agil (Human Resource Management Academic Research Society, 2019)
Social media provides competitive advantages such as enhanced customer relations and services, cost reduction in marketing and customer services, improved information sharing and accessibility, improved brand visibility, revenue generation and competitive advantage. However, in facing these positive developments and changes, the organisation tend to lose control over the dissemination of information. Thus, the organisation will be facing potentials risk such as human error, processes, reputational risk, operational risk, regulatory compliance risk, financial risk and information security risk. To overcome these challenges, organisations need to look and adopt the governance mechanisms by being aware of the policy and risks to ensure that the risks of social media are well managed. Therefore, this study proposes to identify and examine the influence of organization nature and policy awareness, which are key antecedents of adoption of regulatory frameworks and also seek to explain the consequences of the adoption of social media regulatory framework. Specifically, the aim of the study is to identify what are the institutional perspectives on organization culture, awareness and perceived characteristics of regulatory framework as antecedence and its consequences on internal brand. Quantitative method will be adopted for this study. In order to examine the effects of regulatory framework on the internal brand, first, in the stage of item development process (qualitative data), the employee will be interviewed. Second, the questionnaire (quantitative data) will be distributed to the organization staffs for the main survey. Through good governance structure, it will enable and limit individual actions and will help the organization to manage their social media operation successfully. Furthermore, the implementation of social media guidelines or regulatory frameworks is required to protect the organisations’ image and reputation.